Systematic Literature Review: Feasibility of Using the E-Modules in ESD-Based Science Learning in Elementary School - Dwinandha Putri, Febrialita Salma; Sujana, Atep; Kirana, Cut Rania; Istiqomah (International Conference on Elementary Education, 2025)
The level of environmental care attitudes of elementary school students is currently still in the moderate category and not optimal so that integrating environment-based learning through E-Modules into the curriculum can help students understand the importance of ecosystems and the relationship between the environment and humans. This study aims to analyse the feasibility of using E-Modules in ESD-based science learning to train students’ environmental awareness. This type of research is a qualitative study using a systematic literature review research design in terms of inclusion and exclusion criteria. Based on the results of the analysis conducted, 4 articles were obtained that could be studied in depth. In the research conducted, it was found that E-Modules on ESD-based science learning can train and improve environmental care attitudes in elementary school students. Recommendations that can be made for future researchers are to develop ESD-based interactive e-modules with interesting learning methods and develop other science materials.